Analysis of Sales Promotion on Interest in Using Brain Academy by Ruangguru Through Consultative Selling - Melati, Putri; Komariah, Kokom; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The declining quality of education in Indonesia has significant implications, particularly for human resource development. This study investigates the impact of sales promotion on the interest in using Brain Academy by Ruangguru, mediated through consultative selling. The research aims to determine whether sales promotions effectively increase students' interest in utilizing Brain Academy's educational services. Using associative methods and descriptive analysis with a quantitative approach, the study sampled 250 high school students from a population of 6,672 in Sukabumi City, based on data from DAPODIK 2023. Data collection involved observation, interviews, questionnaires, literature studies, and documentation. The analysis utilized Structural Equation Modeling (SEM) with AMOS software. Findings indicate that sales promotion significantly influences consultative selling, which in turn significantly affects students' interest in using Brain Academy. However, direct sales promotion did not significantly influence interest in use. The mediating role of consultative selling was confirmed, demonstrating its importance in effectively translating sales promotions into increased user interest. The study concludes that Brain Academy's marketing strategies should emphasize consultative selling to better address student needs and enhance the effectiveness of sales promotions. These findings provide valuable insights for educational service providers aiming to boost engagement and usage through targeted promotional efforts.